SPECIFIC ASPECTS OF TEACHING THE SCIENTIFIC HERITAGE OF THE JADIDS TO FUTURE HISTORY TEACHERS IN THE METHODOLOGICAL COURSE OF HISTORY TEACHING - Shaturayeva Sevara Tashmuratovna (Sciental Journals Publishing, 2025)
This article examines the specific aspects of teaching the scientific and educational heritage of the Jadid movement to future history teachers within the methodological course of history teaching. The study emphasizes the importance of integrating the ideas of the Jadids—such as enlightenment, modernization, and national identity—into the training of history teachers. It discusses effective pedagogical methods, innovative approaches, and historical thinking strategies that help students understand the progressive role of the Jadids in shaping modern Uzbek education and society. The research also highlights the significance of combining historical content with value-based learning to form professional competence and civic consciousness among future educators.
Keywords: Jadid heritage, history teaching methodology, future history teachers, pedagogical innovation, national identity, enlightenment movement, professional competence, Uzbekistan education system.